Detection of antibodies against Sarcocystis neurona, Neospora spp., and Toxoplasma gondii in horses from Costa Rica - Dangoudoubiyam, S. (2011)
Serum samples from 315 horses from Costa Rica, Central America, were examined for the presence of antibodies against Sarcocystis neurona, Neospora spp., and Toxoplasma gondii by using the surface antigen (SAG) SnSAG2 enzyme-linked immunosorbent assay (ELISA), the NhSAG1 ELISA, and the modified agglutination test, respectively. Anti-S. neurona antibodies were found in 42.2% of the horses by using the SnSAG2 ELISA. Anti-Neospora spp. antibodies were found in only 3.5% of the horses by using the NhSAG1 ELISA, and only 1 of these horses was confirmed seropositive by Western blot. Antibodies to T. gondii were found in 34.0% of the horses tested, which is higher than in previous reports from North and South America. The finding of anti-S. neurona antibodies in horses from geographical areas where Didelphis marsupialis has wide distribution suggests that D. marsupialis is a potential definitive host for this parasite and a source of infection for these horses.